Collaboration in Handling Human Trafficking in The Border Area of NKRI-RDTL: Case Study of North Central Timor Regency - Mbiri, Adeodata Laniria C.B.; Fahik, Yakobus (The Sunan Ampel Review of Political and Social Sciences, 2024)
This study examines cases of human trafficking in TTU Regency by emphasizing cross-sector collaboration in handling human trafficking in TTU Regency. This study is very important because NTT is a province with the highest number of victims of human trafficking in Indonesia and TTU Regency is one of the regencies that contributes to a fairly large number of human trafficking and has increased every year. This study uses the collaboration theory from Ansell & Gash by narrowing it down to 4 indicators, namely: First, Face to Face Dialogue as a communication mechanism; Second, Building Trust and Commitment; Third, Shared Understanding; and Fourth, Intermediate Outcome. This theory is the edge in this study. The research method used is a case study and data collection techniques in the form of observation, interviews, documentation and triangulation. The informants determined in this study are SATGAS TPPO which includes: TTU Regency PPA Office, TTU Regency Manpower and Transmigration Office, Population and Civil Registration Office, TTU Regency Resort Police, TTU Regency Social Service, NGOs, Community leaders, and exmigrants. The analysis technique uses the case study analysis technique from Creswell. The results of the study indicate that in handling Human Trafficking in TTU Regency, collaboration has been carried out with the formation of the TPPO Task Force involving many regional agencies working together, but based on the perspective of Ansell & Gash's theory, this collaboration process has not been optimal in face-to-face implementation so that the process of building trust is minimal but obsessed with high commitment, thus in the implementation of the collaboration that occurs is that each Regional Apparatus Organization included in the TPPO task force tends to have a high sectoral ego and tends to be individualistic in carrying out their respective duties so that the results of this collaboration process are very difficult to evaluate.